Family comes first: Reproductive health and the gender gap in entrepreneurship - Zandberg, Jonathan (Journal of Financial Economics, 2021)
Better access to reproductive healthcare increases women’s propensity to become entrepreneurs. Access correlates positively with female entrepreneurial activity and negatively with female entrepreneurial age. Examining firm size and personal income suggests it also improves the success of female-led businesses. None of these results hold when tested on men, women above 40, or other placebo professions. To establish causality, I exploit Roe v. Wade, state laws restricting abortion providers, and an index tracking state-level regulation of reproductive care. All three analyses suggest that policies securing better reproductive care enable more women to become entrepreneurs. I conclude by discussing various possible channels and mechanisms.